Case report of sequential bilateral spontaneous pneumothorax in a never-ventilated, lung-healthy COVID-19-patient. (2020) - Caviezel, Claudio; Weiss, Lina; Haessig, Gabriela; Alfaré, Christian; Haberecker, Martina; Varga, Zsuzsanna; Frauenfelder, Thomas; Opitz, Isabelle
Highlights: Spontaneous pneumothorax due to COVID-19 may happen in never-ventilated patients. Due to persistence, these pneumothoraces may need surgery for bulla resection. Endothelitis as seen in other organs may contribute to prolonged healing. Abstract: Introduction: Patients with COVID-19 infection and severe lung parenchyma alterations may need mechanical ventilation with subsequent pneumothorax and eventually persistent air leak in case of pre-existing lung disease. Presentation of case: This report presents the case of a never-ventilated 58 years old male patient without pre-existing, underlying lung disease demonstrating severe lung parenchyma changes due to COVID-19-pneumonia. He suffered from recurrent bilateral spontaneous pneumothoraces, which were successfully treated with bilateral thoracoscopy and resections of the destroyed lung areas. Notably, he has already been under treatment with anticoagulation due to portal thrombosis 8 years ago. Discussion: Although especially know from patients under mechanical ventilation, this patient suffered from spontaneous pneumothorax without ever been ventilated. Probably due to the severe vascular inflammatory changes and focal endothelitis like also seen in other organs of COVID-19 patients, the pneumothorax may lead to a prolonged air leak, which needs surgical therapy. The patients pre-existing anticoagulation therapy may prevented him from a mere severe course. Conclusion: Early surgical therapy may be considered in COVID-19 patients with persistent air leak, even if not mechanically ventilated. Simultaneously, the role of early anticoagulation needs further investigation.